Pengaruh Fasilitas Dan Harga Terhadap Repurchase Intention Dimediasi Oleh Kepuasan Pelanggan Di Whiz Prime Hotel Padang - Sari, Putri Yulia; Abrian, Youmil (Departemen Pariwisata Universitas Negeri Padang, 2025)
This study was motivated by the findings of negative reviews related to facilities and prices that were not as expected, which affected customer satisfaction at Whiz Prime Hotel Padang. The purpose of this study was to determine the effect of facilities and prices on repurchase intention mediated by customer satisfaction. This type of research is quantitative research with a survey approach and using the Structural Equation Modeling (SEM) method. The population in this study was 2,983 visitors in the last three months, with a sample of 353 respondents who had stayed at the hotel, selected using purposive sampling. Data collection was carried out by distributing questionnaires via Google Form using a 5-point Likert scale. Data analysis was carried out with the help of SMART PLS version 4.0. The results of the hypothesis test showed that facilities (X1) have a positive and significant effect on customer satisfaction and repurchase intention, with a p-value <0.05. Likewise, price (X2) has a positive and significant effect on customer satisfaction and repurchase intention. In addition, customer satisfaction also has a positive and significant effect on repurchase intention. Based on these results, it can be concluded that facilities and prices have a significant influence on repurchase intention through customer satisfaction